Relationship between psychological well-being and altruistic behaviour in students during the COVID-19 pandemic - Febrianti, Thrisia; Wibowo, Mungin Eddy; Aliyah, Urotul; Susilawati, Susilawati (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to determine the relationship between Psychological well-being and students' altruistic behaviour. The psychological well-being of students is very important to note, this is because it is related to the mood of satisfaction and happiness, especially for students. Altruistic behaviour is a person's volunteerism in helping and helping others. This research was conducted during the COVID-19 pandemic to find out whether there was a relationship between Psychological well-being and Altruistic behaviour during the COVID-19 pandemic. This study involved 175 high school students in Semarang City who were taken using the conventional technique. The instruments used in this study were the Psychological Well Being Scale and the Altruistic Behaviour Scale. This research is a quantitative correlation study and the data were analyzed using descriptive analysis with the help of IBM SPSS for Windows to describe the relationship of Psychological well-being with Altruistic behaviour. The results showed that the overall significance value (Sig = 0.77 > 0.05) so that there was no significant correlation between Psychological Well Being and Altruistic Behaviour.